English Language: Commonly Used Instructional Materials in Teaching and Learning - Ordu, Stanley; Better, Odukwu (Future Science, 2023)
This study investigates the survey of instructional materials commonly used by teachers in teaching and learning of English Language in Selected Junior Secondary Schools in Ogba/Egbema/Ndoni Local Government Area of Rivers State. Five research questions were used to guide the study. The population of the study was 1,230 respondents from Junior Secondary School Students and 120 respondents were used for the study. Twenty five research questionnaires (25) items were raised from the research questions and were analyzed using a four point Likert scale. A benchmark of 2.5 was used as a criterion for agreement. Conclusion and recommendations were made based on the following. Teachers should always try their best to make use of available visual instructional materials necessary to make their lessons more interesting, teachers are encouraged to search for necessary visual instructional materials that can appeal to the sense of learners, arouse their interest, encourage their participation, making learning more meaningful and promote academic standard, school principles should provide teachers with enabling environment for the use of available instructional material to give room for participatory studentship and make learning more meaningful, government should supply teaching aids and finance schools to improvise unavailable and inadequate instructional materials to make teaching and learning easier, practical, appealing and enjoyable.